The Impact of Esports on the Habits, Health, and Wellness of the Collegiate Player - Julie Delello; Rochell McWhorter; Sangok Yoo; Paul Roberts; Beth Adele (Journal of Intercollegiate Sport, 2025)
College students continue to invest a good deal of time in electronic sports despite potential risks such as addiction, health impairment, and social isolation possibly outweighing the benefits of gameplay. This mixed-methods study examines the impact of esports on 38 collegiate gamers and further explores the students’ motivations, gaming habits, and the effects of their engagement on academic performance, social interactions, and overall well-being. It reveals that esports may be beneficial in the formation of friendships, reducing negative peer pressure, and enhancing social capital. Academic advantages are also prominent, with participants reporting improved skills relevant to their coursework, better grades, and an enhanced focus on academics due to the structured nature of esports. However, the study also addresses potential risks, including toxicity, addiction, and adverse health effects like sleep deprivation and stress. Included are critical considerations and policy recommendations for campus esports programs as well as future research directions.